(untitled) (International Journal of Information Technology and Computer Engineering, 2025)
A tumour that grows in the tissues of the breast is called breast cancer. One of the leading causes of death for women worldwide, it is the most common type of cancer found in women. The methods of data mining, deep learning, and machine learning for breast cancer prediction are contrasted in this article. Breast cancer diagnosis and prognosis has been the subject of numerous studies; the accuracy rate of each approach varies according to the situation, tools, and datasets used. In order to identify the most appropriate method for handling massive datasets with high prediction accuracy, our main objective is to compare various current machine learning and data mining approaches.The primary objective of this review is to highlight all of the earlier research on machine learning algorithms used to predict breast cancer. This article gives novices who wish to analyse machine learning algorithms a thorough understanding of deep learning all the information they need.